2010
DOI: 10.1080/17450390903299141
|View full text |Cite
|
Sign up to set email alerts
|

Effect of late gestation low protein supply to mink (Mustela vison) dams on reproductive performance and metabolism of dam and offspring

Abstract: Protein malnutrition in utero that induces permanent changes in metabolism has been investigated intensively in various animals in recent years, but to the best of our knowledge, not yet in the mink, a strict carnivore. In the present study, minks were fed either a low-protein (LP) diet, i.e., with a protein:fat:carbohydrate ratio of 14:51:35% of metabolisable energy (ME), or an adequate-protein diet (AP), i.e. 29:56:15% of ME, from when implantation was completed until parturition (17.9 +/- 3.6 days). Respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
28
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 38 publications
11
28
3
Order By: Relevance
“…The postweaning dietary protein provision was clearly reflected in the N balance data and supported by the OXP during postweaning growth. This was similar to findings among female dams fed an LP or an AP where the amount of dietary protein was also clearly reflected in both the N metabolism and the level of protein oxidation (Matthiesen et al, 2010a).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The postweaning dietary protein provision was clearly reflected in the N balance data and supported by the OXP during postweaning growth. This was similar to findings among female dams fed an LP or an AP where the amount of dietary protein was also clearly reflected in both the N metabolism and the level of protein oxidation (Matthiesen et al, 2010a).…”
Section: Discussionsupporting
confidence: 74%
“…Studies in mink have shown that low protein provision to pregnant dams leads to foetal adaptations, resulting in a lower mRNA expression of some key hepatic gluconeogenic and glycolytic enzymes in both F 1 - (Matthiesen et al, 2010a) and F 2 -generation foetuses (Matthiesen et al, 2010b). These findings indicate that protein provision to the mother plays an important role for the offspring.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations